Work Sectors with High Risk for Work-Related Musculoskeletal Disorders in Korean Men and Women - Jungsun Park; Yangho Kim; Boyoung Han (Elsevier, 2018)
Background: To identify work sectors with high risk for work-related musculoskeletal disorders (MSDs) in Korean men and women. Methods: We analyzed nationwide data to identify ergonomic risk factors in Korean employees. In particular, we analyzed data on exposure to five ergonomic risk factors (painful/tiring postures, lifting/moving heavy materials, standing/walking, repetitive hand/arm movements, and hand/arm vibration) according to employment sector, sex, and age, using the 2014 Fourth Korean Working Conditions Survey. We also used workers' compensation data on work-related MSDs in 2010, which is available by sex. Results: The different work sectors had different gender distributions. "Manufacturing" (27.7%) and "construction" (11.3%) were dominated by males, whereas "human health and social work activities" (12.4%), "hotel and restaurants" (11.7%), and "education" (10.4%) were dominated by females. However, "wholesale and retail trade" and "public administration and defense" employed large numbers of males and females. Furthermore, the work sectors with a greater proportion of work-related MSDs and with multiple ergonomic risk factors were different for men and women. For men, "construction" and "manufacturing" had the highest risk for work-related MSDs; for women, "hotel and restaurants" had the highest risk for work-related MSDs. Conclusion: Ergonomic interventions for workers should consider gender and should focus on work sectors with high risk for MSDs, with multiple ergonomic risk factors, and with the largest number of workers. Keywords: ergonomic, risk factor, Korean workers, musculoskeletal disorder